2009
DOI: 10.1007/s11103-009-9470-5
|View full text |Cite
|
Sign up to set email alerts
|

Spermine facilitates recovery from drought but does not confer drought tolerance in transgenic rice plants expressing Datura stramonium S-adenosylmethionine decarboxylase

Abstract: Polyamines are known to play important roles in plant stress tolerance but it has been difficult to determine precise functions for each type of polyamine and their interrelationships. To dissect the roles of putrescine from the higher polyamines spermidine and spermine, we generated transgenic rice plants constitutively expressing a heterologous S-adenosylmethionine decarboxylase (SAMDC) gene from Datura stramonium so that spermidine and spermine levels could be investigated while maintaining a constant putre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…This could be due to the translational or post-translational regulation of these genes, as previously shown (Carbonell and Blázquez 2009;Alcázar et al 2010;Mattoo et al 2010;Shao et al 2011). Also, in previous studies, overexpression of the PA biosynthetic genes such as SAMDC or SPDS has been shown to bring about very limited accumulation of Spd and/or Spm (Wen et al 2008;Peremarti et al 2009), which may be ascribed to tight homeostatic regulation of these PA at the cellular level. Therefore, the mature-fruit abscission is accompanied by decreased OeSPD1 and OeSAMDC1 gene expression, parallel to SAMDC activity …”
Section: Mature-fruit Abscission Changes Pa Biosynthesis Transcript Pmentioning
confidence: 74%
See 1 more Smart Citation
“…This could be due to the translational or post-translational regulation of these genes, as previously shown (Carbonell and Blázquez 2009;Alcázar et al 2010;Mattoo et al 2010;Shao et al 2011). Also, in previous studies, overexpression of the PA biosynthetic genes such as SAMDC or SPDS has been shown to bring about very limited accumulation of Spd and/or Spm (Wen et al 2008;Peremarti et al 2009), which may be ascribed to tight homeostatic regulation of these PA at the cellular level. Therefore, the mature-fruit abscission is accompanied by decreased OeSPD1 and OeSAMDC1 gene expression, parallel to SAMDC activity …”
Section: Mature-fruit Abscission Changes Pa Biosynthesis Transcript Pmentioning
confidence: 74%
“…Changes in plant PA biosynthetic enzyme activities and gene expression are regulated separately, depending on physiological and developmental conditions (Bagni and Tassoni 2001;Kusano et al 2008;Carbonell and Blázquez 2009;Shao et al 2011), and SAMDC was found to be an important enzyme in the regulation of PA homeostasis (Kusano et al 2008;Mattoo et al 2010). As the cellular PA content can be regulated at the transcriptional level, it is possible to modulate the endogenous PA level via overexpression of the PA biosynthetic genes, as has been previously revealed (Mehta et al 2002;Wen et al 2008;Peremarti et al 2009;Nambeesan et al 2010).…”
Section: Introductionmentioning
confidence: 72%
“…It has been found that an Arabidopsis mutant plant that does not produce Spm was hypersensitive to drought stress (Kusano et al 2007). Spd plays a role as intermediate by indirectly maintaining high Spm content during abiotic stress, but accumulated Spd content in plants might get also converted into Put (Roychoudhury et al 2011;Peremarti et al 2009). Higher (Spd ?…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the Spd levels in the transgenic lines were moderate (1.3-to 2-fold higher), yet the susceptibility to B. cinerea was greatly increased. Moderate changes in PA levels, especially increases in Spd, have been shown to cause significant physiological changes in transgenic Arabidopsis, rice (Oryza sativa), and pear (Pyrus communis) plants overexpressing SpdSyn and SAMdc genes (Kasukabe et al, 2004;Wen et al, 2008;Peremarti et al, 2009). Unsuccessful attempts to obtain stable transgenic potato plants expressing a potato SAMdc under the CaMV35S promoter, while SAMdc antisense lines led to a range of stunted phenotypes also support this contention (Kumar et al, 1996).…”
Section: Discussionmentioning
confidence: 99%